Climatic and evolutionary factors shaping geographical gradients of species richness in Anolis lizards - Velasco, Julián A.; Villalobos, Fabricio; Diniz-Filho, José Alexandre F.; Algar, Adam C.; Flores-Villela, Oscar; Köhler, Gunther; Poe, Steven; Martínez-Meyer, Enrique (Linnean Society, 2018)
Understanding the climatic and historical factors shaping species richness is a major goal of ecology and biogeography. Consensus on how climate affects species richness is still lacking, but four potential and non-exclusive explanations have emerged: water-energy, where diversity is determined by precipitation and/or temperature; seasonality, where diversity is determined by seasonal variation in climate; heterogeneity, where diversity is determined by spatial variability in climate; and historical climatic stability, where diversity is determined by changes in climate through evolutionary time. Climate–richness relationships are also mediated by historical processes such as phylogenetic niche conservatism and lineage diversification across regions. We evaluated the effect of climate on species richness gradients of Anolis lizards and tested the role of phylogenetic niche conservatism (PNC) and regional diversification (RD) in the origin and maintenance of climate-richness relationships. Climate had a strong non-stationary relationship with species richness with strong shared effects among several climate axes. Regional differences in climate–richness relationships suggest different assembly processes between regions. However, we did not find evidence for a role of evolutionary factors such as PNC or RD underlying these relationships. We suggest that evolutionary processes affecting climate-richness relationships in Anolis likely were obscured by high dispersal rates between regions.